Development of Family Medicinal Gardens (TOGA) through the Tato Macan Program to Strengthen Community Health and Economic Resilience - Pasila, Naomi Shinta; Nurbeliana, Erwin; Pratiwi, Sarah Dhea; Priono, Rodhi Dwi; Relatami, Andi N Renita; Dwinhoven, Ifhan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The Tato Macan Program (Taman TOGA Makin Cantik) is part of Prokesmas Puja, an integrated community health initiative. It focuses on improving health and economic resilience by making better use of Family Medicinal Gardens (TOGA).The program was created to address two key issues: idle land that was not being utilised productively and the need for additional nutrition for tuberculosis patients and children at risk of stunted growth. Activities include transforming unused land into TOGA demo gardens, training health cadres and local people to cultivate and process herbal plants, and creating value-added products such as herbal teas, packaged jamu, and moringa chips.In line with circular economy principles, the program also promotes composting organic waste and using biogas to support production. These efforts have led to the development of stronger skills among health cadres and community members, the growth of model TOGA gardens, and the establishment of new micro-enterprises specialising in herbal products. Families benefit directly through extra income and reduced household expenses.Beyond its local impact, Tato Macan has inspired other communities through knowledge sharing, helping the program spread more widely. In short, it contributes to health by offering functional foods, to society by empowering cadres, and to the economy by diversifying community businesses. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 5: Gender EqualitySDG 12: Responsible Consumption and ProductionSDG 13: Climate Action